Pott’s Puffy Tumour – Rare and Forgotten, yet Relevant and Life-Threatening: Case Report - Phukan, Himraj; Lynser, Donboklang; Lyngwa, Gareth Yobel; Daniala, Chhunthang; Barman, Himesh; Ghosh, Tamajyoti (Acta medica Lituanica, 2025)
Pott’s Puffy Tumour (PPT) is an inflammation and swelling of the forehead secondary to osteomyelitis of the frontal bone. Multiple aetiologies are associated with this condition, predominately involving a prior sinus surgery or a direct trauma to the frontal bone. There can be intracranial extension with an epidural, subdural as well as intracerebral abscess. We present the case of an 8-year-old boy who presented with swelling in his forehead secondary to trauma. His general condition was poor, and further evaluation revealed multiple subdural empyemas. Although PPT is rare in this modern era of antibiotics, it should be kept as a differential for any inflammation of the forehead. Timely diagnosis and the appropriate treatment by a multidisciplinary team are indispensable in reducing the morbidity and mortality associated with this case.